Hptlc fingerprint profile, isolation and validation of marker compound lupeol in derris heyneana (wight and arn) benth - APARNA SARAF; POOJA SHINDE (International Journal of Pharma and Bio Sciences, 2016)
The present study was aimed at identification, isolation and quantification of marker compound Lupeol in Derris heyneana (Wight and Arn) Benth. by using HPTLC. A simple and sensitive High-Performance Thin-Layer Chromatographic (HPTLC) method validation was carried out as per the ICH guidelines for the identification and quantification of biomarker lupeol in root, stem and leaves of Derris heyneana (Wight and Arn) Benth. Different mobile phases were tried out of which Toluene: Ethyl acetate: glacial Acetic acid: formic acid (12:6.1:1 (v/v)) gave good separation at 540nm after derivatization with anisaldehyde sulphuric acid reagent. Highest amount of lupeol was found in stem. The linearity range was found to be 0.1 µg to 0.7µg/ spot. The Rf was found to be 0.68±3. The method was validated using ICH guidelines in terms of Linearity, precision, specificity and accuracy. The fingerprint developed can strongly be recommended for the purpose of quality control of marketed medicinal plant and phytopreparations.